Implementasi Kebijakan “Mappadeceng” Dalam Bidang Pendidikan di Kabupaten Soppeng - Tri Cahyo Nugroho; Suriadi Lambali; Hamsina Hamsina (Kolaborasi : Jurnal Administrasi Publik, 2023)
This study aims to analyze the implementation of the "Mappadeceng" policy in the education sector in Soppeng Regency by using descriptive qualitative methods. Data was collected by means of in-depth interviews, observation, and documentation of 6 informants. Data analysis was performed interactively consisting of data reduction, data presentation and drawing conclusions. The results show that the implementation of the "mappadeceng" policy in the education sector has not been going well, this is because the size and policy objectives are not yet clear, the availability of human resources and budget is adequate, the implementing agency has a role based on the stipulated decree, the disposiion of implementing agents it is good enough, the lack of communication and coordination carried out, both with the community and related organizations and the external environment consisting of economic, social and political conditions is quite conducive and supports the implementation of the “mappadeceng” policy. Therefore, it is recommended that the education and culture office of Soppeng Regency to conduct evaluation in increasing the success of implementing the “Mappadeceng” policy.